THE EFFECT OF WAGES, WORK FACILITIES, AND OCCUPATIONAL SAFETY AND HEALTH SYSTEMS ON EMPLOYEE PERFORMANCE AT PT BOCOROCCO TANGERANG - Pujiyati, Rina; Zurnali, Cut; Qodariah, Qodariah (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This study aims to analyze the effect of wages, work facilities, and occupational safety and health systems on employee performance at PT Bocorocco Tangerang. Employee performance is an important factor that affects the productivity and success of the company. In this study, the independent variables tested include wages, work facilities, and occupational safety and health, while the dependent variable is employee performance. The method used in this study is a quantitative approach using data obtained through questionnaires distributed to 78 employees of PT Bocorocco Tangerang. Data analysis was carried out using SEM PLS, to determine the extent to which each independent variable affects employee performance. The results of the study indicate that wages, work facilities, and occupational safety and health have a positive and significant effect on employee performance. These findings indicate that increasing fair wages, adequate work facilities, and attention to occupational safety and health can increase employee motivation and productivity. Therefore, companies are expected to pay more attention to these aspects to improve employee performance and support the achievement of company goals.